Stochastic heating of charged particles - Buts, V.A.; Kuzmin, V.V.; Tolstoluzhsky, A.P. (Вопросы атомной науки и техники, 2013)
Comparison of two schemes of heating of charged particles is provided – at interaction with the field of wave with chaotically changing phase and with the field of the regular wave in the conditions of overlapping of non-linear resonances. Efficiency of heating at fulfillment of conditions of the resonances overlapping in all considered cases is more effective.